Urgensi Peran Notaris dalam Menjamin Legalitas Transaksi Elektronik: Tinjauan Hukum Jabatan Notaris (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the urgency of the role of notaries in ensuring the legality of electronic transactions in Indonesia. Along with the rapid development of technology, electronic transactions are increasingly being carried out in various sectors, including in legal agreements and contracts. Although Law No. 11 of 2008 concerning Electronic Information and Transactions (UU ITE) provides a legal basis for electronic transactions, challenges still arise in its implementation, especially related to the recognition of electronic documents as valid evidence in court. In this case, the role of notaries becomes very important, because notaries have the authority to validate electronic documents and ensure that transactions are carried out in accordance with applicable legal provisions. This study uses a qualitative literature study method to gain an in-depth understanding of existing regulations, challenges faced, and the role of notaries in validating electronic transactions. Thus, notaries not only function to validate documents, but also to provide legal protection for parties involved in electronic transactions.